Nessuna disciplina si salva da sola. Diario di un’etnografia in Antartide #1 - Elena Bougleux (Archivio Antropologico Mediterraneo)
Antarctic research stations can only be reached and inhabited thanks to research projects. The Antarctic Treaty establishes a special, supranational legal status for the entire continent, inspired by scientific research, environmental protection and collaboration. The ongoing research projects that I have been observing for about a month, finding myself in one of the Italian bases managed by the PNRA, are all built around a basic multi-disciplinarity, which involves the fundamental knowledge of natural sciences. The project that brings me to Antarctica is also a multidisciplinary one, but in a broader, deeper and more critical sense, which puts me in the privileged position of observing macro-processes and micro-dynamics that contribute in a non linear way to the construction of knowledge.